Intercambiar en Mesoamérica durante el Epiclásico (600 a 900 d.C.): poder, prestigio y alteridad. Un análisis de la cultura material de Puebla-Tlaxcala y Morelos (México) - Juliette Testard (Journal de la Société des Américanistes, 2018)
Through the study of supraregional interactions among four capitals of the Mexican highlands, and sites of the Gulf coast and Maya area during the Epiclassic period (AD 600 to 900), several hypotheses may be proposed concerning a possible shift in political paradigm at that time. Analysed with a specific methodology, portable and non-portable material artefacts and associated iconographic corpus, are discussed in terms of theories bearing on political action documented in Mesoamerica resulting in convergent lines of evidence. Within a context of ideological, social and political disruptions following the end of Teotihuacán, new elites of these cities in sporadic contact with those of distant societies exerted their power thanks to glorification of persons, exacerbation of military force and prestige acquired through distant interactions.